Synchrotron radiation from the magnetoplasma - Shukla P.K.; Singh K.P.; Singh R.N. (My University, 2025)
Numerical studies of the synchrotron radiation from relativistic elections in the magnetoplasma are presented. Effects of a background medium on the synchrotron radiation is considered by moans of a solar corona model. We demonstrate that the low-frequency radiation is suppressed. © 1973 Taylor and Francis Ltd.